Occurrence of the Cowpea aphid-borne mosaic virus in Jataí, Brazil - Gomes, Francielly Rodrigues; Marques Costa, Marcelo; Celeste Carneiro, Luciana; Marques de Almeida Spadotti, David; da Assunção, Hildeu Ferreira; Pereira da Silva, Danielle Fabíola (Comunicata Scientiae, 2021)
The objective was to characterize the introduction of the passion fruit woodiness disease in plants and fruits of passion fruit in Jataí - GO. Plants of passion fruit showed the symptoms of the virus at the end of the first year in the field. Infection was confirmed by serological analysis using the PTA ELISA indirect test. This report will contribute to the information already known about this disease, and will serve as a basis for passion fruit producers to identify symptoms in plants affected with the virus.